Label-free tracking of single organelle transportation in cells with nanometer precision using a plasmonic imaging technique - Yang, Yunze (Small, 2015)
Imaging and tracking of nano- and micron-sized organelles in cells with nanometer precision is crucial for understanding cellular behaviors at the molecular scale. Because of the fast intracellular dynamic processes, the imaging and tracking method must also be fast. In addition, to ensure that the observed dynamics is relevant to the native functions, it is critical to keep the cells under their native states. Here, we demonstrate a plasmonics-based imaging technique for studying the dynamics of organelles in three dimensions (3D) with high localization precision (5 nm) and temporal (10 ms) resolution. The technique is label-free and can track subcellular structures in the native state of the cells. Using the technique, we have successfully observed nanometer steps of organelle (e.g., mitochondria) transportation along neurite microtubules in primary neurons, and reconstructed the 3D structure of neurite microtubule bundles at the nanometer scale from the tracks of the moving organelles.